Impact of product-package design on material waste due to stock-induced consumption phenomenon. (24th September 2020) - Sharma, Neeta; Vrat, Prem
This paper attempts to examine the impact of product-package design in influencing the consumption behaviour due to stock-induced consumption phenomenon. The exploratory research presented in this paper shows how a design feature in a product or packaging can enhance consumption rate over the normal consumption resulting in waste. It also reports the findings of primary research data collected through controlled condition experimentation on two consumable products from FMCG category - toothpaste and shampoo. It is shown that a bigger orifice size results in extra consumption in tubed or bottled products and the discounts offered by the manufacturer on bigger size products may be more than offset by the excess stock-induced consumption due to orifice size. The orifice size and product viscosity play significant role in controlling stock-induced material waste. The paper suggests the need for standardisation of orifice size and product viscosity to minimise the material waste in such products. Additionally, this research explores the effect of instantaneous volumetric stock availability for consumption in toothpaste tube on its consumption rate and attempts to estimate stock-dependent consumption parameters α and β for the consumption of toothpaste.